2019
DOI: 10.1163/22125892-00701007
|View full text |Cite
|
Sign up to set email alerts
|

The deviant typological profile of the Tocharian branch of Indo-European may be due to Uralic substrate influence

Abstract: Tocharian agglutinative case inflexion as well as its single series of voiceless stops, the two most striking typological deviations from Proto-Indo-European, can be explained through influence from Uralic. A number of other typological features of Tocharian may likewise be interpreted as due to contact with a Uralic language. The supposed contacts are likely to be associated with the Afanas’evo Culture of South Siberia. This Indo-European culture probably represents an intermediate phase in the movement of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…However, although Afanasievo-related ancestry has been confirmed among Iron Age Dzungarian populations (around 200–400 bc ) 7 , and Tocharian is recorded in Buddhist texts from the Tarim Basin dating to ad 500–1000 (ref. 13 ), little is known about earlier Xinjiang populations and their possible genetic relationships with the Afanasievo or other groups.…”
Section: Mainmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although Afanasievo-related ancestry has been confirmed among Iron Age Dzungarian populations (around 200–400 bc ) 7 , and Tocharian is recorded in Buddhist texts from the Tarim Basin dating to ad 500–1000 (ref. 13 ), little is known about earlier Xinjiang populations and their possible genetic relationships with the Afanasievo or other groups.…”
Section: Mainmentioning
confidence: 99%
“…1 and Extended Data Table 1 ). These and related Bronze Age sites are grouped within the Xiaohe archaeological horizon on the basis of their shared material culture 13 , 16 , 20 .…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, archaeological and mitochondrial studies have suggested that the BA inhabitants and cultures of Xinjiang were not derived from any indigenous Neolithic substrate but rather from a mix of West and East Eurasian people ( 5 , 13 , 14 ), whereas BA burial traditions suggest links with both North Eurasian Steppe cultures and the Central Asian BMAC civilization ( 15 ). Linguistically, the presence of the now-extinct Indo-European Tocharian language, attested to in ~5th to 10th century CE texts from the Tarim Basin, also raised questions regarding the origin and extent of Indo-European–speaking people in Xinjiang ( 7 , 15 ). To date, one mitochondrial study of the BA Xiaohe site in the Tarim Basin found evidence of both Steppe- and central Siberian–derived haplogroups and only a later influence from the BMAC ( 13 ), whereas a broader mitochondrial survey indicated that these results may not apply to the region as a whole ( 14 ).…”
mentioning
confidence: 99%
“…traversed from the west through the Inner Asian Mountain Corridor (IAMC), and millet (~4000 B.P.) is presumed to have entered Xinjiang from the east through the Hexi Corridor (3)(4)(5)7). An understanding of the origins of the BA inhabitants of Xinjiang is necessary to follow the changes that these cultural and technological transfers have had on the population structure over the ensuing millennia.…”
mentioning
confidence: 99%